Comparative Analysis of Organic and Chemical Pesticides: Impacts on Crop Health and Environmental Sustainability - Priyanka , Kadam; Yadav, Birendra Singh; Kote , Ashwini; Yadav , Rohan; Shejwal, Pooja (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Pesticides are indispensable tools in modern agriculture, aiding in the protection of crops against pests and diseases. Nevertheless, the adverse effects of chemical pesticides on human health and the environment have catalyzed a shift towards organic alternatives. This review critically assesses the use of both organic and chemical pesticides, evaluating their respective impacts on crop health and environmental sustainability. We delve into aspects such as efficiency, safety, environmental footprint, and regulatory frameworks surrounding these two types of pesticides, drawing insights from recent research. By synthesizing current knowledge, our aim is to provide a comprehensive understanding of the advantages and limitations of organic and chemical pesticides, empowering stakeholders to make informed decisions towards sustainable agricultural practices.